199k views
2 votes
1. Find (f*g)(x) if
f(x)= -6x+11 and g(x)=3x-5.

User Mrtnmgs
by
5.4k points

1 Answer

7 votes

Answer:

(f * g)(x) = -18x² + 63x - 55

General Formulas and Concepts:

Algebra

  • Expand by FOIL (First Outside Inside Last)
  • Terms/Coefficients/Degrees

Explanation:

Step 1: Define

f(x) = -6x + 11

g(x) = 3x - 5

(f * g)(x) is f(x) · g(x)

Step 2: Find

  1. Substitute: (f * g)(x) = (-6x + 11)(3x - 5)
  2. Expand [FOIL]: (f * g)(x) = -18x² + 30x + 33x - 55
  3. Combine like terms: (f * g)(x) = -18x² + 63x - 55
User MasterGberry
by
4.3k points